Review of illegal betting as financial crime in web forensics - Sönmez, Yeşim Ülgen; Varol, Asaf (Institute of Electrical and Electronics Engineers Inc., 2018)
Throughout the world, there are debates and questionnaires on whether sports betting is morally wrong and whether it should be legal or illegal. While these debates continue every nationwide, governments are updating the laws on betting. They bring different criminal sanctions-like fault and offense-to betting bosses and betting players in both physical and virtual environments. Illegal betting harms countries' economies because money transfer is among the different countries. It also directs people to the gambling. For this reason, illegal betting is an important concept in information law and computer forensics. There can be many criminals or criminal tendencies in web activities, as well as illegal betting. This study reviews illegal betting in terms of information law and web forensics. © 2018 IEEE.
6th International Symposium on Digital Forensic and Security, ISDFS 2018 -- 22 March 2018 through 25 March 2018 -- Antalya -- 136277
Keywords: financial crime; Illegal betting; web forensics